Extensive logging in miombo woodlands threatens resource Nexus potential for diverse values of nature: lessons from Dzalanyama Forest Reserve in Malawi - Makwinja, Yamikani Harry; Mkhwimba, Dalitso (Frontiers in Forests and Global Change, 2025)
Logging in protected areas is widely acknowledged as a sustainability dilemma, as it sits at the centre of conservation and community livelihood goals. But is this position supported by scientific evidence? Our study used Dzalanyama Forest Reserve in Malawi as a case study to (1) examine the effects of logging on tree species diversity, (2) determine community perceptions on drivers of logging, and (3) explore the impact of logging on the water-energy-biota-soil (WEBS) nexus. To achieve this, we employed an explanatory sequential mixed methods approach. Our study showed that (a) extensive logging in protected forest areas reduces tree species diversity. We observed that the alpha (α) tree species diversity in the least logged and most logged areas did not differ significantly (p > 0.05). However, the beta (β) species diversity between the least and most logged sites differed significantly at a 95% confidence level, with Shannon indices of 2.55 and 1.15, respectively. (b) We reported corruption as the primary driver of logging, as perceived by local communities, with a weighted average index of 0.092, followed by weak law enforcement (0.088) and energy poverty (0.087). (c) Logging in protected areas significantly weakens the WEBS Nexus. We reported a positive correlation between tree species diversity and WEBS Nexus. These results suggest that extensive logging in Miombo woodlands reduces resource Nexus synergies while increasing trade-offs. Therefore, understanding the dynamics of forest resources triggered by logging in protected areas may inform policy direction and guide sustainable forest management planning.